Pemahaman Baru Pembajakan Digital dalam Budaya Mengopi (Praktik dan Implikasi Budaya Mengopi Video di Warnet di Yogyakarta) - , IRHAM NUR ANSHARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Since a few years back, copying video has become a common practice at several cybercafes in Yogyakarta. The practice grows in such a way so it became a culture that deserved to be studied. The present research aims at documenting the video copying culture in Yogyakarta, understanding the implication of that culture on video distribution and consumption, and re-understanding the digital-piracy in the contemporary global media context.Using a new ethnographic approach, data were collected through interviewing the informant consisting of some identified video-copying actors. The data were also collected by observing the involved cybercafes and their documented information. The obtained data were then analyzed using the combination of piracy theories from two perspectives: media product as commodity perspective (the theories by Lawrence Lessig, 2004, 2008 and Joe Karaganis, 2011) and media product as cultural product perspective (the theories by Joost Smiers, 2009